Grain-cropping suitability for evaluating the agricultural land use change in Brazil. (May 2023) - Safanelli, José Lucas; Nóia Júnior, Rogério de Souza; Coutinho, Pedro Alves Quilici; Araujo, Marcela Almeida de; Fendrich, Arthur Nicolaus; Rizzo, Rodnei; Chamma, Ana Letícia Sbitkowski; Tavares, Paulo André; Barretto, Alberto Giaroli de Oliveira Pereira; Maule, Rodrigo Fernando; Reichardt, Klaus; Sparovek, Gerd; et al.
Abstract: Mapping and monitoring tools are imperative in assessing agricultural systems and guiding future decision-making to safeguard food security. Since grain-croplands are the main occupation within the Brazilian croplands that has played a substantial role in the country's land use/land cover (LULC) dynamic, this study aims at proposing a grain-cropping suitability index (CroppingSI) to support the geographical analysis of LULC agricultural trends. The proposed approach considers detailed information on climate, soils, and terrain coupled with grain-crop simulations, soil quality indexing, and terrain restrictions evaluated at the highest available resolution. With historical LULC maps (2000 and 2020), we found that terrain was the most critical factor for cropland expansion, followed by climate and soil quality. The new croplands expanded towards regions with better climate and terrain conditions while neglecting the soil quality, mostly in the Cerrado and Amazon regions. In addition, the assessment of CroppingSI was instrumental in understanding that expanding new croplands over current cleared areas (i.e., pasturelands) may expose them to marginal soil and terrain conditions. This suggests a fragility of the current expansion trend of grain-cropping systems which can substantially put food security at risk, requiring alternative strategies for maintaining or improving food through crop intensification. Highlights: Biophysical determinants of grain-cropland expansion were determined. Croplands have been expanding towards better climate and terrain conditions. The expansion has been taking place mostly over Cerrado and Amazon biomes. The expansion, however, has been neglecting soil quality.